DAMPAK EFEKTIVITAS DAN EFISIENSI BELANJA PEMERINTAH DAERAH SEKTOR KESEHATAN DAN EKONOMI TERHADAP KESEJAHTERAAN MASYARAKAT DI PULAU JAWA - Gigih Surya Prakasa; Agustina Suparyati (Media Ekonomi, 2022)
This study aims to analyze the effectiveness and efficiency of regional government spending in the health and economic sectors to public welfare on the island of Java. The effectiveness of regional spending in the health and economic sectors is measured by the achievement of Minimal service standards of health and the realization of regional spending on gross regional domestic income, while the efficiency of regional spending is measured by the realization of regional expenditures on the Regional Budget. This research was designed as a research with a quantitative approach. The public welfare which is the dependent variable in this study is measured through the Human Development Index. This data research use sample of 99 regencies/cities in West Java, Central Java, and East Java during 2012-2016 sourced from the Ministry of Finance, the Central Statistics Agency, and the Provincial Health Office. The analysis was carried out through a panel data regression model with a Fixed Effect Model approach. The results of the analysis show that the achievement of Minimal Service Standards of Health and Regional Expenditures on Gross Regional Domestic Revenue has a positive effect on the growth of the Human Development Index, while the realization of local government spending on the Regional Revenue and Expenditure Budget has a negative effect on the growth of the Human Development Index. It is necessary to make improvements to the indicators of Minimal Service Standards in the Health sector. In addition, regional government spending needs to be encouraged for spending that has a direct effect on increasing the Human Development Index